THE EFFECT OF FISHBOWL TECHNIQUE ON THE SPEAKING ABILITY OF THE FIRST YEAR STUDENTS OF SMAN 12 PEKANBARU - Siti Khusriyah; Fakhri Ras; Desri Maria Sumbayak (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aimed to find out whether there is a significant effect of fishbowl technique on the speaking ability of the first year students of SMAN 12 Pekanbaru. This is a pre-experimental research conducted by using a pre-test – treatment – post-test design. The instrument administered in this research was oral speaking tests (pre-test and post-test). The population of this research was 420 of the first year students of SMAN 12 Pekanbaru and the sample of this research is the X4 of social science class of SMAN 12 Pekanbaru. The total number of students is 36 students. The collected data were analyzed by operating statistical analysis in form of SPSS 23.0 in order to compare the results of students’ speaking ability in the pre-test and post-test. The results of data analysis showed that the mean score of pre-test was 55.26, and the mean score of post-test was 69.74. Based on the data analysis, it can be concluded that there is a significant difference between the pre-test and the post-test because the t-test observed was higher than t-table. In other words, the alternative hypothesis of this research was accepted. It means that teaching speaking by fishbowl technique was effective to improve students’ speaking ability.Key Words : Speaking Ability, Fishbowl technique